Rock Force : the American paratroopers who took back Corregidor and exacted MacArthur's revenge on Japan - Maurer, Kevin (Dutton Caliber, Penguin Random House, 2020)
"In late December 1941, General Douglas MacArthur, caught off guard by the Japanese invasion of the Philippines, is forced to retreat to Corregidor, a jagged, rocky island fortress at the mouth of Manilla Bay. Months later, under orders from the president, the general is whisked away in the dark of night, leaving his troops to their fate. It is a bitter pill for a fiercely proud warrior who has always protected his men. He famously declares "I shall return," but the humiliation of Corregidor haunts him, even earning him the derisive nickname "Dugout Doug." In early 1945, MacArthur returns to the Philippines, his eyes affixed firmly on Corregidor. To take back the island, he calls on the 503rd Parachute Infantry Regiment, a highly-trained veteran airborne unit. Their mission is to jump onto the island--hemmed in by sheer cliffs, pockmarked by bomb craters, bristling with deadly, spiky, broken tree trunks--and wrest it from some 6,700 Japanese defenders who await, fully armed and ready to fight to the death. Drawn from firsthand accounts and personal interviews with the battle's surviving veterans, acclaimed war correspondent and bestselling author Kevin Maurer delves in this extraordinary tale, uncovering astonishing accounts of bravery and heroism during an epic, yet largely forgotten, clash of the Pacific War. Here is an intimate story of uncommon soldiers showing uncommon courage, and winning, through blood and sacrifice, the redemption of General MacArthur"--